STRATEGI PEMASARAN BANK MUAMALAT KANTOR CABANG PEMBANTU (KCP) KOTA METRO - Arifin, Hasan (Universitas Muhammadiyah Metro, 2024)
The purpose of this research is to find out what marketing strategies are most appropriate to be used by Bank Muamalat KCP Metro in marketing their products. The analysis method uses SWOT and AHP. The results of the SWOT analysis show Bank Muamalat KCP Metro is in a position to grow and develop with the right marketing strategy is an intensive strategy (market development, market concentration and product development). From the analysis using AHP, the alternative strategy chosen is market penetration strategy with a PV value (0.391). That way the right marketing strategy for Bank Muamalat KCP Metro is the market penetration strategy.